2021
DOI: 10.3390/ma14051180
|View full text |Cite
|
Sign up to set email alerts
|

Geopolymer Recycled Aggregate Concrete: From Experiments to Empirical Models

Abstract: Ordinary cement concrete is a popular material with numerous advantages when compared to other construction materials; however, ordinary concrete is also criticized from the public point of view due to the CO2 emission (during the cement manufacture) and the consumption of natural resources (for the aggregates). In the context of sustainable development and circular economy, the recycling of materials and the use of alternative binders which have less environmental impacts than cement are challenges for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 33 publications
(36 reference statements)
3
8
0
Order By: Relevance
“…The contents of coarse and fine aggregates did not seem to have a significant effect on strength. This trend was in line with the findings of previous studies, where it was reported that the interface transition zone (ITZ), morphology and particle size distribution of the aggregates was more influential in strength development than their contents [30,54]. Finally, Table 7 elucidates the effect of pre-curing on the compressive strength of FA-based geopolymer concrete, revealing the role pre-curing plays in improving the minimum, average and maximum strength values of all data sets.…”
Section: Effects Of Different Input Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…The contents of coarse and fine aggregates did not seem to have a significant effect on strength. This trend was in line with the findings of previous studies, where it was reported that the interface transition zone (ITZ), morphology and particle size distribution of the aggregates was more influential in strength development than their contents [30,54]. Finally, Table 7 elucidates the effect of pre-curing on the compressive strength of FA-based geopolymer concrete, revealing the role pre-curing plays in improving the minimum, average and maximum strength values of all data sets.…”
Section: Effects Of Different Input Parameterssupporting
confidence: 89%
“…However, the dynamic increase factor obtained from the constitutive model presented in this study was not consistent with the experimental results. Le et al [30] used the modified Feret and De Larrard models to predict the compressive strength of FA-based geopolymer recycled aggregate concrete. Compared with Feret's model, which requires a modification that replace the parameter for cement (C) with the parameter for binder (B) to ensure reasonable prediction accuracy, De Larrard's model only needs to determine the parameters of natural and recycled aggregates in advance to get satisfactory prediction results.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 17 shows the scanning electron micrographs of the geopolymer concrete samples exposed to 200, 800, and 1000 • C. At 200 • C, the microstructures of the geopolymer concrete sample are characterized by a dense and intact morphology with little pore spaces (Figure 17a,b). Similarly, dense and flat microstructures were observed in fly-ash-based geopolymer concrete researched by Zhao et al [79] and Le et al [80]. Zhao et al [79] further discovered that that the dense microstructure of the geopolymer concrete remained intact after an exposure to 400 • C. After an exposure to 800 • C, however, some thermal micro-cracks could be seen in the microstructures of the geopolymer concrete samples (Figure 17c,d).…”
Section: Morphological and Chemical Properties Of Durable Geopolymer ...supporting
confidence: 57%
“…At 200 °C, the microstructures of the geopolymer concrete sample are characterized by a dense and intact morphology with little pore spaces ( Figure 17 a,b). Similarly, dense and flat microstructures were observed in fly-ash-based geopolymer concrete researched by Zhao et al [ 79 ] and Le et al [ 80 ]. Zhao et al [ 79 ] further discovered that that the dense microstructure of the geopolymer concrete remained intact after an exposure to 400 °C.…”
Section: Morphological and Chemical Properties Of Durable Geopolymer ...mentioning
confidence: 53%
“…Therefore, some alternatives have been made towards minimizing the direct utilization of natural sources for aggregates as well as reducing environmental concern regarding increases in by-products with limited landfills available, which will consequently lead to pollution of the environment. Further initiatives to mitigate the depletion of natural resources include the introduction of recycled aggregates and artificial aggregates, which encourages the recycling of waste materials [ 15 , 24 , 25 ].…”
Section: Geopolymers As Artificial Aggregatesmentioning
confidence: 99%